2016
DOI: 10.2147/tcrm.s121928
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Th1/Th2 cytokine profiles and chest radiographic manifestations in childhood<em> Mycoplasma pneumoniae</em> pneumonia

Abstract: BackgroundMycoplasma pneumoniae pneumonia (MPP) is one of the most common childhood community-acquired pneumonias, and the chest radiograph usually shows bronchial pneumonia, segmental/lobar pneumonia, or segmental/lobar pneumonia with pleural effusion. The imbalance of Th1/Th2 function after Mycoplasma pneumoniae infection is an important immunological mechanism of MPP. In this study, we aimed to evaluate the correlations between Th1/Th2 cytokine profiles and chest radiographic manifestations in MPP children.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 34 publications
3
22
0
Order By: Relevance
“…Additionally, IL-6s in RMPP patients were significant higher than those in General MPP patients [19] . IL-6 was also associated with pleural effusion [20] and radiological appearance [8] in MPP patients. Guo L et al reported that IL-6s in serum of patients infected by macrolide-resistant strains were higher than those infected by non macrolideresistant strains [21] .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, IL-6s in RMPP patients were significant higher than those in General MPP patients [19] . IL-6 was also associated with pleural effusion [20] and radiological appearance [8] in MPP patients. Guo L et al reported that IL-6s in serum of patients infected by macrolide-resistant strains were higher than those infected by non macrolideresistant strains [21] .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, IL-6 in RMPP patients was significant higher than that in the General MPP patients [19] . IL-6 was also associated with pleural effusion [20] and radiological appearance [8] in MPP patients. Guo L et al reported that IL-6s in serum of patients infected by the macrolide-resistant strains were higher than those infected by non macrolide-resistant strains [21] .…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that proinflammatory cytokines IL-2, TNF- α , and IL-6 were simultaneously involved in MP pneumonia, in the progress of which Th1 cytokines (IL-2 and TNF- α ) were upregulated and Th2 cytokine (IL-6) was downregulated, thereby changing the balance of Th1/Th2 toward Th1 cells. A Th1/Th2 balance function plays a significant role in anti-infectious immunity and the response of Th1/Th2 cytokines are useful biomarkers in diagnosis and treatment of MP infection in children with pulmonary involvement [ 47 , 48 ]. Our studies demonstrated that the imbalance of the Th1/Th2 function after Mycoplasma pneumoniae infection is an important immunological mechanism of MP pneumonia.…”
Section: Discussionmentioning
confidence: 99%